Pacific Rim [videorecording (DVD)] - Elba, Idris; Hunnam, Charlie, 1980-; Kikuchi, Rinko, 1981-; Day, Charlie; Perlman, Ron, 1950-
When legions of monstrous creatures, known as Kaiju, started rising from the sea, a war began. On the verge of defeat, the forces defending mankind have no choice but to turn to two unlikely heroes-a washed up former pilot and an untested trainee, who are teamed to drive a legendary but seemingly obsolete Jaeger from the past. Together, they stand as mankind's last hope against the mounting apocalypse.